Physicians’ knowledge, attitude, and practice regarding medicolegal and ethical aspects of telemedicine use in Cairo, Egypt: lessons from the COVID-19 pandemic - Magda M. Ramdan; Sonya M. S. Azab; Tasneem R. Shaaban; Hanan E. Salem (Egyptian Journal of Forensic Sciences)
Abstract Background Healthcare professionals have been using telemedicine for a long time; yet, it was not until the outbreak of the COVID-19 epidemic that it was widely adopted. As telemedicine has expanded, related legal and ethical issues have emerged and the concerns about its regulation are increasing. Therefore, the purpose of the study was to evaluate doctors' understanding, attitudes, and practices regarding the use of telemedicine and its ethical and legal implications. Results This cross-sectional study was conducted on physicians with different specialties. Data was gathered using an online, self-administered, structured questionnaire. The questionnaire was distributed via an open-access Google survey to physicians through social media and professional networks from November 2021 to June 2022, ensuring anonymity and voluntary participation. The respondents were 434 physicians working in healthcare settings in Cairo, Egypt. Consultation of an expert was the most common purpose of using telemedicine by the participants (93.8%, n = 407), followed by medical education (81.1%, n = 352), and management of the patients (73%, n = 317). Regarding physicians’ knowledge, the majority (94.2%, n = 409) demonstrated an understanding of their responsibility to maintain the confidentiality of patients' information. However, a significant proportion (54.4%, n = 236) were unaware that patients retain the right to pursue legal action against a physician if they experience medical harm while utilizing telemedicine services. Considering physicians’ attitudes toward the advantages of telemedicine, the majority (80.7%, n = 350) expressed agreement that telemedicine facilitates remote communication between healthcare providers and patients. In the scope of physicians’ practice, 37.7% of the respondents (142 physicians) reported an incidence of complications related to telemedicine use. The most commonly reported cause of complications was a patient’s inability to describe his/her condition (97%, n = 244). Conclusions Due to concerns about medical liability, the majority of doctors employ telemedicine in addition to face-to-face patient interaction. Because telemedicine involves communicating via social networks and platforms that do not ensure data protection, and because patient data is stored on mobile devices, maintaining the confidentiality of patient information may be difficult. It is recommended to establish a national e-health organization to oversee telemedicine services and issue licenses to telemedicine practitioners.